Cloud Atlas - Guo, Ting (The journal of religion and film, 2013)
This is a film review of Cloud Atlas (2012) which aims to address what constitutes the reasons for the success of this film and the humanistic theme in which they are rooted, despite the seemingly Buddhist philosophy such as reincarnation this film embodies.